Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together Terhadap Hasil Belajar Keliling dan Luas Bangun Datar di Sekolah Dasar - Sutrisno, Laras Purdi; Lena, Mai Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This research aimed to determine the effect of cooperative learning model type numbered head together on students’ learning outcomes on circumference and area of geometry at grade 4 of Elementary School II Luhak Nan Duo. This research is quantitative research with experimental method and Quasi Experiment Design, it used Non-equivalent control group design. The sampling technique used was cluster random sampling. The data were analyzed using t-test. The results showed that the the average of post-test in experiment class was 77.4 and 69.4 in control class. Analysis of t-test both in experiment and control classes  was obtained tcount = 3.302 and ttable = 2.011 at a significant level of 0.05. Hence tcount>ttable then Ha was accepted. Thus it can be concluded that cooperative learning model type of Numbered Head Together  had positive effect on the circumference and area of geometry at grade 4  in Elementary School II Luhak Nan Duo.